The Influence of Product Quality, Service Quality and Perceived Quality on Repurchase Intention with Customer Satisfaction as Intervening Variables at XXYZ Surabaya Store Customers - Pastikan Vision Boi Tebulo Laia; Sri Handini (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2022)
Abstract. Product quality is the result of the production of a product that can be a factor in sales volume. Meanwhile, service quality is the totality of features and characteristics of a product or service that bears on its ability to satisfy stated or implied needs. In addition to product quality and service quality, there is perceived quality, namely the customer's perception of the overall quality or superiority of a product or service related to what is expected by the customer. The hypothesis of this study states that the three variables, namely, product quality, service quality and perceived quality affect repurchase intentions directly and indirectly through the intervening variable, namely satisfaction. This research was conducted on exhaust fan products owned by the XXYZ brand. This study uses a quantitative approach with data collection methods using questionnaires. This study uses the PLS method using SmartPLS3. Respondents in this study were XXYZ Surabaya customers who had purchased exhaust fan products in the period March 2019-March 2021 with age over 30 years. The number of respondents in this study amounted to 100 respondents. The results of this study explain that the independent variables namely product quality, service quality and perceived quality have a significant influence on the intervening variable, namely satisfaction. For the independent variable perceived quality has no direct effect on repurchase intention. And the product quality variable has no indirect effect on repurchase intention.Keywords: Product quality; service quality; perceived quality; satisfaction; repurchase intention